Characterization and history of the Helmi streams with Gaia DR2 - Koppelman, Helmer H.; Bastian, Ulrich (Astronomy and astrophysics, 2019)
Context. The halo of the Milky Way has long been hypothesized to harbour significant amounts of merger debris. For more than a decade this view has been supported by wide-field photometric surveys which have revealed the outer halo to be lumpy.Aims. The recent release of Gaia DR2 is allowing us to establish that mergers also have been important and possibly built up the majority of the inner halo. In this work we focus on the Helmi streams, a group of streams crossing the solar vicinity and known for almost two decades. We characterize their properties and relevance for the build-up of the Milky Way’s halo.Methods. We identify new members of the Helmi streams in an unprecedented dataset with full phase-space information combining Gaia DR2, and the APOGEE DR2, RAVE DR5, and LAMOST DR4 spectroscopic surveys. Based on the orbital properties of the stars, we find new stream members up to a distance of 5 kpc from the Sun, which we characterized using photometry and metallicity information. We also perform N-body experiments to constrain the time of accretion and properties of the progenitor of the streams.Results. We find nearly 600 new members of the Helmi streams. Their HR diagram reveals a broad age range, from ≈11 to 13 Gyr, while their metallicity distribution goes from −2.3 to −1.0, and peaks at [Fe/H] ∼ −1.5. These findings confirm that the streams originate in a dwarf galaxy. Furthermore, we find seven globular clusters to be likely associated, and which follow a well-defined age-metallicity sequence whose properties suggest a relatively massive progenitor object. Our N-body simulations favour a system with a stellar mass of ∼108 M⊙ accreted 5 − 8 Gyr ago.Conclusions. The debris from the Helmi streams is an important donor to the Milky Way halo, contributing ≈15% of its mass in field stars and 10% of its globular clusters.
Gesehen am 04.06.2019